The novel positive colossal electroresistance in PbPdO2 thin film with (002) preferred orientation. Issue 19 (1st October 2021) - Jia, Hai; Chen, Yue; Lin, Chun; Ruan, Yurong; Chen, Shuiyuan; Zhang, Jian-Min; Huang, Zhigao
Abstract: Doped PbPdO2 materials have attracted much attention as a spin gapless semiconductor (SGS) with the important properties of colossal electroresistance (CER) and giant magnetoresistance (GMR). In this study, the PbPdO2 thin films with (002) preferred orientation were prepared by pulsed laser deposition (PLD), and the temperature dependences of resistance and resistivity, R ( T ) and ρ I ( T ), were measured under different applied DC currents. Remarkably, a positive CER effect induced by the current was firstly observed in the PbPdO2 films. In particular, it is novelty found that the positive CER value of PbPdO2 with I = 10 μA and T = 10 K reached about 300%. Moreover, the cyclic ρ I ( T ) curves were also measured for I = 0.01 and 10 μA going back and forth between 10 K and 400 K. The time dependences of ρ t /ρ 0 ratio with T = 100 K, 300 K, 400 K and I = 0.01 and 0.1 μA were also obtained. A critical temperature T c with about T = 260 K for all applied currents was found. As T > T c ，the band gap of the film is enhanced by the combined effect of the temperature and current. At the same time, Pb and O vacancies, and the evolution of oxygen valence states in the PbPdO2 film were observed by energy dispersive spectrometer (EDS), electron paramagnetic resonance (EPR) and in-situ x-ray photoelectron spectroscopy (XPS). Especially, the charge transport between O 1− and O 2− was confirmed by in-situ XPS. Finally, based on first-principles calculation, an internal electric field model and its induced potential barrier were established, which well explains the positive CER effect and the critical temperature T c .